Implemetasi Algoritma Base64 dan Algoritma Discrete Consine Transform Dalam Penyisipan Gambar Terenkripsi Pada Audio Digital - M. Rian Warisman Sinaga; Guidio Leonarde Ginting (Journal of Information System Research (JOSH), 2020)
Types of multimedia that are developed and known by all groups, namely photos, videos, images, moving to images can be inserted into audio and so forth. Piracy of information or data in the type of multimedia that is confidential is often revealed to the public and known to the public. Based on these problems, it is necessary to secure information in the form of images using Cryptography. Cryptography is knowledge or skill that observes and examines how to encrypt images that are in the owner's secret to remain safe and cannot be duplicated which is guaranteed and confidentiality is maintained. Based on these problems we need a base 64 algorithm that has an encryption process to be able to help secure an image or information that is confidential. DCT algorithm is able to liken an image or information with very strong security